High-resolution single-cell RNA sequencing using canFam4 reveals novel immune subsets and checkpoint programs in healthy dogs - Kim, Myung-Chul; Gu, Taeeun; Seo, Hyeewon; Moon, Yewon; Borcherding, Nicholas; Kolb, Ryan; Kim, Yubin; Yun, Youngmin; Song, Woo-Jin; Lee, Chung-Young; Kim, Hyun Je; Zhang, Weizhou (Frontiers in Immunology, 2025)
IntroductionSingle-cell RNA sequencing (scRNA-seq) enables high-resolution profiling of immune heterogeneity. Although previous studies have mapped the single-cell transcriptomic atlases of peripheral leukocytes in healthy dogs, the identification and functional characterization of distinct immune subsets remain incomplete.MethodsWe constructed a single-cell atlas of peripheral leukocytes from six healthy small-breed dogs using the 10x Genomics platform and the updated canFam4 genome.Results and discussionAnalysis of 30,040 high-quality transcriptomes revealed 51 distinct immune subsets, including CD14+CD33+ monocytes, XCR1+CD1D+ dendritic cells, CEACAM1+CD24+ neutrophils, and IL32+BATF+ regulatory T cells, which were underrepresented in canFam3.1-based studies. Interferon-enriched CD14+ monocytes and CD4+ T subsets associated with myxomatous mitral valve disease were also identified. Functional enrichment analyses suggested that PDCD1 is associated with attenuated TCR signaling, whereas LAG3 was associated with malate metabolism pathways in CD4+ T cells and reduced TBX21 expression in CD8+ T cells linked to antiviral responses. CD274, which encodes PD-L1 was linked to IL-10 production in neutrophils, and CTLA4 represented an initial activation of double-negative T subsets. T cell exhaustion scores and proliferative fractions varied across cohorts, reflecting differences in environmental antigenic exposures.ConclusionTo our knowledge, this study represents the first comprehensive, gene-resolved single-cell analysis to reveal immunoregulatory checkpoint mechanisms underlying immune homeostasis in healthy dogs. Our dataset will serve as a valuable resource for future comparative and translational immunology research in dogs.